Knowledge of antibiotics and antibiotic usage behavior among the people of Dhaka, Bangladesh - Ahmed, Iftekhar; Rabbi, Md Bodiuzzaman; Rahman, Marufa; Tanjin, Rehnuma; Jahan, Sharmin; Khan, Md Abu Adnan; Sultana, Sakina (Asian Journal of Medical and Biological Research, 2020)
Bangladesh is a developing country with a very high prevalence of antibiotic resistance where irrational use of antibiotics is very common. This cross-sectional survey was conducted to assess the knowledge of antibiotics and antibiotic usage behavior (Antibiotic use, self-medication, adherence to therapy) among the people of Bangladesh. The association between participants’ knowledge of antibiotics and their antibiotic usage behavior was also analyzed. A cross-sectional survey based on a structured questionnaire was conducted in the Dhaka district. The questionnaire included questions about demographic information, participants’ knowledge of antibiotics, and their recent antibiotic usage. The data analysis involved the use of descriptive statistics and multivariable logistic regression. Very few participants knew that antibiotics are not effective against most common colds (16.8%), viruses (22.5%), and pains (41.7%). Most respondents (>75%) knew that excessive use of antibiotics and failing to complete a course may render antibiotics less effective in the future. However, only 56.1% were aware of antibiotic resistance. About half (46.6%) of the participants took antibiotics in the last six months, 20.5% of whom resorted to self-medication and 23.1% reported non-adherence to therapy. Greater knowledge of antibiotics was significantly associated with lower rates of self-medication (p=0.037). Misconceptions about antibiotics and antibiotic misuse are very common in Bangladesh. The findings suggest that misconceptions about antibiotics and antibiotic misuse are very common in Bangladesh. To mitigate these problems, interventions comprised of educational campaigns and redesigning of the healthcare system and policies should be undertaken. Asian J. Med. Biol. Res. September 2020, 6(3): 519-524